Effects of cellular senescence on metabolic pathways in non-immune and immune cells. (March 2021) - Frasca, Daniela; Saada, Yara Bou; Garcia, Denisse; Friguet, Bertrand
Highlights: Senescent cells are metabolically active. Cellular senescence induces metabolic changes in non-immune and immune cells. Senescent cells are flexible in the use of different metabolic pathways. Metabolic reprogramming in senescent cells leads to increased survival and supports function. Abstract: Many cellular stresses induce cellular senescence and the irreversible arrest of cell proliferation in different cell types. Although blocked in their capacity to divide, senescent cells are metabolically active and are characterized by a different metabolic phenotype as compared to non-senescent cells. Changes observed in senescent cells depend from the cell type and lead to an adaptative flexibility in the type of metabolism. This metabolic reprogramming is needed to cope with survival and with the energetic demands of the senescent program that include the increased secretion of senescence-associated secretory phenotype factors.